IMPLEMENTASI INTERNATIONAL LABOUR ORGANIZATION CONVENTION 182 TAHUN 1999 TENTANG PENGHAPUSAN BENTUK PEKERJAAN TERBURUK ANAK JALANAN DI KOTA MAKASSAR: IMPLEMENTATION OF INTERNATIONAL LABOR ORGANIZATION CONVENTION 182 1999 REGARDING THE Abolition of the Worst Forms of Work STREET CHILDREN IN MAKASSAR CITY - Claudia Soenjoyo, Cindy; A. Hasan, Yulia; Rusli, Muhammad (Faculty Of Law Bosowa University, 2021)
This study aims to determine: 1) To what extent is the implementation of the 182 Year International Labor Organization (ILO) Convention Konvensi1999 on the worst forms of street child work in Makassar City; 2) Program Realization Street Children Developmentin Makassar City. The research method used is empirical normative research. Research location in Makassar City. Techniques and data collection through literature and interviews. Research results, 1) Implementation International Labor Organization Convention 182 of 1999 which was passed into Law No.1 of 2000 is not Indonesia's last step in fulfilling legal protection for children. The protection provided by the government is further realized by the existence of Article 74 of Law No. 13 of 2003 concerning Manpower and Law No. 23 of 2002 concerning Child Protection but was changed to Law No. 35 Year 2014. 2) The realization of Makassar City government programs, namelycontinued development, social rehabilitation efforts, exploitation, empowerment, further guidance, and community participation.